2017
DOI: 10.1111/ped.13278
|View full text |Cite
|
Sign up to set email alerts
|

Training program for Japanese medical personnel to combat child maltreatment

Abstract: Professionals from a range of fields need clinical skills and judgement to decide if a child's injuries are due to maltreatment. The combination of increased clinical experience along with a high-quality didactic lecture, appears to be the most effective method of raising awareness and enhancing skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Approximately one-third of the participants in the study reported that they had encountered child abuse and neglect or a suspicious situation in their work lives so far. healthcare professionals, the baseline scores of the participants who had previously received training to deal with child maltreatment were found to be higher than those who had not previously received training (Tanoue et al, 2017). In a compilation work examining the effectiveness of the training aimed at identifying and improving the management of child abuse and neglect, it was reported that there were various educational models on this subject, and that all of them had positive effects, however that their superiority over each other and long-term results should be evaluated (Carter, 2006).…”
Section: Opinions On Situation Preventing Reporting Of Child Abuse An...mentioning
confidence: 85%
“…Approximately one-third of the participants in the study reported that they had encountered child abuse and neglect or a suspicious situation in their work lives so far. healthcare professionals, the baseline scores of the participants who had previously received training to deal with child maltreatment were found to be higher than those who had not previously received training (Tanoue et al, 2017). In a compilation work examining the effectiveness of the training aimed at identifying and improving the management of child abuse and neglect, it was reported that there were various educational models on this subject, and that all of them had positive effects, however that their superiority over each other and long-term results should be evaluated (Carter, 2006).…”
Section: Opinions On Situation Preventing Reporting Of Child Abuse An...mentioning
confidence: 85%
“…Japan created a similar educational program for medical institution personnel to combat child maltreatment in 2014. [12] The questionnaire included 12 statements designed to ascertain respondents’ practical knowledge and attitudes relevant to addressing child maltreatment. They compared baseline scores determined before the lecture with those obtained after the lecture.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the scores for practical knowledge addressing child maltreatment improved significantly and became higher than the baseline scores scores (11.18 vs 10.57; t = À9.94, P < .01). [12] The United Kingdom (UK) has also developed a child abuse educational program for pediatric residents. The Level I program, "Safeguarding Children: Recognition and Response in Child Protection," was launched nationally in the UK as an educational program for pediatricians in education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations